Unveiling the Angiotensin-(1–7) Actions on the Urinary Bladder in Female Rats - Lamy, Gustavo B.; Cafarchio, Eduardo M.; do Vale, Bárbara; Antonio, Bruno B.; Venancio, Daniel P.; de Souza, Janaina S.; Maciel, Rui M.; Giannocco, Gisele; Silva Neto, Artur F.; Oyama, Lila M.; Aronsson, Patrik; Sato, Monica A. (Frontiers in Physiology, 2022)
Angiotensin-(1–7) is a peptide produced by different pathways, and regardless of the route, the angiotensin-converting enzyme 2 (ACE-2) is involved in one of the steps of its synthesis. Angiotensin-(1–7) binds to Mas receptors localized in different cells throughout the body. Whether angiotensin-(1–7) exerts any action in the urinary bladder (UB) is still unknown. We investigated the effects of intravenous and topical (in situ) administration of angiotensin-(1–7) on intravesical pressure (IP) and cardiovascular variables. In addition, the Mas receptors and ACE-2 gene and protein expression were analyzed in the UB. Adult female Wistar rats were anesthetized with 2% isoflurane in 100% O2 and submitted to the catheterization of the femoral artery and vein for mean arterial pressure (MAP) and heart rate (HR) recordings, and infusion of drugs, respectively. The renal blood flow was acquired using a Doppler flow probe placed around the left renal artery and the renal conductance (RC) was calculated as a ratio of Doppler shift (kHz) and MAP. The cannulation of the UB was performed for IP recording. We observed that angiotensin-(1–7) either administered intravenously [115.8 ± 28.6% angiotensin-(1–7) vs. −2.9 ± 1.3% saline] or topically [147.4 ± 18.9% angiotensin-(1–7) vs. 3.2 ± 2.8% saline] onto the UB evoked a significant (p < 0.05) increase in IP compared to saline and yielded no changes in MAP, HR, and RC. The marked response of angiotensin-(1–7) on the UB was also investigated using quantitative real-time polymerase chain reaction and western blotting assay, which demonstrated the mRNA and protein expression of Mas receptors in the bladder, respectively. ACE-2 mRNA and protein expression was also observed in the bladder. Therefore, the findings demonstrate that angiotensin-(1–7) acts in the UB to increase the IP and suggest that this peptide can be also locally synthesized in the UB.